Anatomy of the female pelvic nerves: a macroscopic study of the hypogastric plexus and their relations and variations. Issue 3 (19th May 2020) - Aurore, Valerie; Röthlisberger, Raphael; Boemke, Nane; Hlushchuk, Ruslan; Bangerter, Hannes; Bergmann, Mathias; Imboden, Sara; Mueller, Michael D.; Eppler, Elisabeth; Djonov, Valentin
Abstract: The autonomic nerves of the lesser pelvis are particularly prone to iatrogenic lesions due to their exposed position during manifold surgical interventions. Nevertheless, the cause of rectal and urinary incontinence or sexual dysfunctions, for example after rectal cancer resection or hysterectomy, remains largely understudied, particularly with regard to the female pelvic autonomic plexuses. This study focused on the macroscopic description of the superior hypogastric plexus, hypogastric nerves, inferior hypogastric plexus, the parasympathetic pelvic splanchnic nerves and the sympathetic fibres. Their arrangement is described in relation to commonly used surgical landmarks such as the sacral promontory, ureters, uterosacral ligaments, uterine and rectal blood vessels. Thirty‐one embalmed female pelvises from 20 formalin‐fixed and 11 Thiel‐fixed cadavers were prepared. In all cases explored, the superior hypogastric plexus was situated anterior to the bifurcation of the abdominal aorta. In 60% of specimens, it reached the sacral promontory, whereas in 40% of specimens, it continued across the pelvic brim until S1. In about 25% of the subjects, we detected an accessory hypogastric nerve, which has not been systematically described so far. It originated medially from the inferior margin of the superior hypogastric plexus and continued medially into the presacral space. The existence of an accessory hypogastric nerve was confirmed during laparoscopy and by histological examination. The inferior hypogastric plexuses formed fan‐shaped plexiform structures at the end of both hypogastric nerves, exactly at the junction of the ureter and the posterior wall of the uterine artery at the uterosacral ligament. In addition to the pelvic splanchnic nerves from S2–S4, which joined the inferior hypogastric plexus, 18% of the specimens in the present study revealed an additional pelvic splanchnic nerve originating from the S1 sacral root. In general, form, breadth and alignment of the autonomic nerves displayed large individual variations, which could also have a clinical impact on the postoperative function of the pelvic organs. The study serves as a basis for future investigations on the autonomic innervation of the female pelvic organs. Abstract : At dissection of the autonomic nerves of the female lesser pelvis, in about 25% of specimens, an accessory hypogastric nerve running medially into the presacral space was detected. Complex vegetative fibres observed underline the necessity to further study the interplay of autonomic pelvic innervation.